Greek Minority in Albania: Exclusion or Inclusion? - Sako, Marsela (Mediterranean Journal of Social Sciences, 2012)
The collapse of the communist bloc meant, the direction of former communist countries toward systems withdemocratic structure. The processes of radical transformations in the economy and politics, made the societies of thesecountries face with major challenges and problems. With the restoration of freedom and human rights, almost all Eastern blocsocieties were confronting problems carrying in itself the issue of minorities, considered as destabilizing factors in the case ofpoor management. Given this, the paper aims to review some of the key trends and policies toward national minorities inAlbania, as part of the Balkans, focusing particularly on the Greek minority that constitute the minority with the largestpopulation. The focus of attention to the Albanian legislation will give us a clearer picture of the rights and freedoms that areguaranteed to minorities in Albania, and the spaces that were created for inclusion in the government level and to influence thevarious decision-making processes. Research of this issue covers the period 1990-2006.